Poissons du Paléogène inférieur de Silveirinha (Portugal) - Antunes, M. Telles (2010)
Fragmentary skeletal remains of Percoid fishes (Teleostei, Percoidei) are described from the Upper Paleocene? or Lowermost Eocene(MN7) from Silveirinha. It is suggested that they belong to some primitive Percoids which are already known in the Iberian peninsula. They bear witness of an ancient westwards extension of the geographical distribution of Percoid fishes that are common in the lower levels of the Eocene in the Douro Basin in Spain.